Prevalence of Hypochondriasis Disorder among Iraqi Former Prisoners of Iraq-Iran War, 1980-1988 - Ibrahim, maan (Iraqi National Journal of Nursing Specialties, 2007)
Objective : To find out the prevalence of Hypochondriasis among Iraqi repatriated prisoners ofIraq-Iran war, and the relationship with some variables.Methodology: A descriptive study was carried out from Jan. 2nd , 2006 through May 4th , 2006. Anon-probability accidental sample of 400 repatriates who had visited; Ministry of Human Rights,Ministry of Health, and Ministry of Defense. A questionnaire was constructed for this purpose, whichconsisted of 6 items for demographic data, and 14 items for measuring Hypochondriasis. Reliabilityand validity of the questionnaire had been determined through the pilot study (Test and retest) and theexperts panel. Data were collected with using the constructed questionnaire and the process of theinterview as means for data collection. Data were analyzed through the application of descriptivestatistical analysis, which are; percentages, frequencies and inferential statistic analysis (Pearsoncorrelation coefficient).Results: The study revealed that the majority of repatriates are inflicted with moderate and severelevels of Hypochondriasis. The findings also indicated that there is a high significant relationshipbetween Hypochondriasis relative to; duration of captivity, marital status, level of education, and dateof repatriation.Recommendations: The study recommends that it is very important to establish special mental healthservices centers within the primary health care centers deal with those repatriates for counseling and inorder to diagnose and treat them and further studies in this field with follow-up studies for the.